已知|a+1/2|+(b-3)^2=0,求[(2x+b)^2]-(b+2a)(2a-b)-6b]÷2b的值
1个回答
提示:
|a+1/2|+(b-3)^2=0
|a+1/2|=0,a=-1/2
(b-3)^2=0,b=3
求[(2x+b)^2]-(b+2a)(2a-b)-6b]÷2b的值,我相信你会的!
相关问题
已知|a-1|+(b+4)^2=0,求[(2a+b)^2-(2a+b)(2a-b)-6b]÷2b的值
已知(2a-1)2+|3b-1|=0,求[(a+b)2-(a-b)2+6a2b3]÷(-2ab)的值.
已知|a-2|+(b+4)^2=0 求[(2a+b)^2-(2a+b)(2a-b)-6b]÷2b的值
已知|a+[1/2]|+(b-3)2=0,求代数式[(2a+b)2+(2a+b)(b-2a)-6b]÷2b= ___ .
已知|a+[1/2]|+(b-3)2=0,求代数式[(2a+b)2+(2a+b)(b-2a)-6b]÷2b= ___ .
已知3a^2+2ab-2b^2=0,求a÷b-b÷a-(a^2+b^2)÷ab的值.
已知|3a-b+1|+(3a-[3/2]b)2=0 求b2a+b÷[([b/a−b])•([ab/a+b])]的值.
已知根号2a-1+|b+2|=0,求(2a+b)(2a-b)+b(2a+b)-4a^2b÷b的值
已知|a+1/2 |+b^2-6b+9=0,求代数式[(2a+b)^2+(2a+b)(b-2a)-6ab]÷2b
1,已知a^2+2a+b^2-6b+10=0,求a^b的值 2,已知a-b=-2,b-c=3.求a^2+b^2+c^2-